Does terrorism work? : a history - English, Richard, 1963- (Oxford, United Kingdom ; New York, NY : Oxford University Press, 2016)
"Terrorism is one of the most significant security threats that we face in the twenty-first century. Not surprisingly, there is now a plethora of books on the subject, offering definitions of what terrorism is and proffering advice on what causes it and how states should react to it. But one of the most important questions about terrorism has, until now, been left remarkably under-scrutinized: does it work? Richard English now brings thirty years of professional expertise studying terrorism to the task of answering this complex--and often controversial--question. Focusing principally on four of the most significant terrorist organizations of the last fifty years (al-Qaida, the Provisional IRA, Hamas, and ETA), and using a wealth of sources, including interviews with former terrorists and with people involved in counterterrorism, he argues that we need a far more honest understanding of the degree to which terrorism actually works--as well as a more nuanced insight into the precise ways in which it does so"--Provided by publisher.
Introduction -- Jihadist Terror : The Case of al-Qaida -- Ireland and the Provisional IRA -- Hamas and Palestinian Terrorism -- Basque Terrorism, ETA, and the Spanish State -- Conclusion.
Includes bibliographical references (pages 323-344) and index.
PPDM, ARC
Karim International
Self-Renewing
Keywords: Qaida (Organization); Provisional IRA; Ḥarakat al-Muqāwamah al-Islāmīyah.; ETA (Organization); Qaida (Organization); Provisional IRA; Ḥarakat al-Muqāwamah al-Islāmīyah.; ETA (Organization); ETA (Organization); Ḥarakat al-Muqāwamah al-Islāmīyah.; Provisional IRA; Qaida (Organization); Terrorism -- History; Terrorism -- Evaluation; Security, International; Security, International; Terrorism; 89.58 political violence; Society; History